THE EPIDEMIOLOGICAL PROFILE OF PATIENTS HELD A DIABETES MELLITUS REGISTERED IN THE HIPERDIA PROGRAM OF A BASIC HEALTH UNIT IN THE STATE OF RIO DE JANEIRO - Capita Quarto, Lucas; Maria da Fonseca Souza, Sônia; Felipe da Silva Lopes, João; Luiz Teixeira Fully, Fábio; Crispim França Luquetti, Eliana (LINKSCIENCEPLACE, 2026)
Diabetes mellitus is among the most prevalent chronic disabling diseases in the world, thus becoming a global epidemic. The high frequency of this pathology, especially in the elderly population, can trigger a series of complications compromising the quality of life and health of the patients. In view of this scenario, the present study aims to analyze the epidemiological profile of patients with diabetes mellitus enrolled in the Hiperdia program of a Basic Health Unit in the state of Rio de Janeiro. This is a descriptive exploratory research. Patients with diabetes mellitus enrolled in the Basic Health Unit are mostly female, have type 2 diabetes, with a family history and low schooling. In addition to diabetes mellitus, the majority also presented with hypertension and overweight. Given the results achieved, it can be seen that diabetes mellitus is a common problem in the daily lives of many individuals. Knowledge of the epidemiological profile of these patients could help the employees of the Basic Health Unit under study to create actions directed to the monitoring and monitoring of the disease, through more effective actions regarding prevention and control. Adequate control of diabetes mellitus will contribute to the quality of life of those affected, being essential to reduce the costs of the disease.